PENGARUH PENGETAHUAN, PERSEPSI, DAN LINGKUNGAN MAHASISWATERHADAP MINAT MAHASISWA MENJADI PENGURUS BEM FEB UPGRIS: Studi Kasus Pada Mahasiswa FEB UPGRIS Angkatan 2017-2020 - Ristianto Wahyudi Irwan; Rauly Sijabat; Ratih Hesty Utami Puspitasari (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to determine the effect of students 'knowledge, perceptions and environment on students' interest in becoming the BEM FEB UPGRIS management. Respondents in this study were students of the Faculty of Economics and Business, University of PGRI Semarang with a sample of 267 students. The data collection process was carried out by distributing questionnaires via google form media to all students of the Faculty of Economics and Business from class 2017-2020. This research is using quantitative methods. Methods of data collection using stratified random sampling technique using a questionnaire. This study uses multiple linear regression analysis using statistical test tools. The data processing of this study used IBM SPSS 22 tools. The results of this study indicate that there is a positive and significant influence between knowledge on student interest, and perceptions do not have a positive and significant effect on student interest, and the student environment has a positive and significant effect on student interest. Knowledge, perceptions, and the student environment together have an effect on student interest. knowledge has an effect of 63% on student interest, perception of 0.29% and student environment by 31%. Based on the results of the research that has been done, the value of Adjusted R Square is 0.740 or 74%.